2016
DOI: 10.1016/j.jphs.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Polaprezinc reduces paclitaxel-induced peripheral neuropathy in rats without affecting anti-tumor activity

Abstract: Paclitaxel, an anticancer drug, frequently causes painful peripheral neuropathy. In this study, we investigated the preventive effect of polaprezinc on paclitaxel-induced peripheral neuropathy in rats. Polaprezinc (3 mg/kg, p.o., once daily) inhibited the development of mechanical allodynia induced by paclitaxel (4 mg/kg, i.p., on days 1, 3, 5 and 7) and suppressed the paclitaxel-induced increase in macrophage migration in dorsal root ganglion cells. In addition, polaprezinc did not affect the anti-tumor activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…After activation, NF-κB regulates the expression of genes such as those encoding the inflammatory cytokines TNF-α, IL-1, and IL-6 that can directly or indirectly affect microvascular endothelial cells or blood cells to mediate their interaction, which leads to the dysfunction of microcirculation, endothelial cell, and tissue injury. 18…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After activation, NF-κB regulates the expression of genes such as those encoding the inflammatory cytokines TNF-α, IL-1, and IL-6 that can directly or indirectly affect microvascular endothelial cells or blood cells to mediate their interaction, which leads to the dysfunction of microcirculation, endothelial cell, and tissue injury. 18…”
Section: Resultsmentioning
confidence: 99%
“…After activation, NF-jB regulates the expression of genes such as those encoding the inflammatory cytokines TNF-a, IL-1, and IL-6 that can directly or indirectly affect microvascular endothelial cells or blood cells to mediate their interaction, which leads to the dysfunction of microcirculation, endothelial cell, and tissue injury. 18 Ohata et al, 19 found that PZ protects against lipopolysaccharide-induced endotoxin shock via inhibition of NF-jB activation and subsequent induction of proinflammatory products including NO and TNF-a. In the present study, we show that the levels of NF-jB in the brain increased significantly after rats were administered CTX or DDP alone.…”
Section: Effects Of Px Combined With Ctx or Ddp On The Gastric Mucosamentioning
confidence: 99%
“…Induction of neuropathic pain and dosing PTX (4 mg/kg) was injected intraperitoneally (i.p.) in volumes of one ml per kg, four times a week (on days 1, 3, 5, and 7) [32]. PTX dose selection was presumed on a previous report [32].…”
Section: Methodsmentioning
confidence: 99%
“…in volumes of one ml per kg, four times a week (on days 1, 3, 5, and 7) [32]. PTX dose selection was presumed on a previous report [32]. 1 was administered once daily for 8 days (5 and 10 mg).…”
Section: Methodsmentioning
confidence: 99%
“…Inflammatory cytokines (e.g., interleukin-1 beta (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α)) and chemokines (e.g., chemokine (C-X-C motif) ligand (CXCL) family) were elevated in the peripheral sites, spinal cord, and of paclitaxeltreated animals, and many agents reduced the peripheral neuropathy symptoms via their anti-inflammatory effects [19,21,22,24,25,27,28,[32][33][34][35][36][37][38][39]41,42,[44][45][46][47][49][50][51][52][53][54]56]. Activations of astrocytes and microglia were also observed in the spinal dorsal horn after paclitaxel administrations, and many agents including minocycline attenuated PIPN via the inhibition of these spinal changes and prevented neurological damage [40,43,44,48].…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%